Clinical manifestations, diagnosis, and treatment of ischemic mitral regurgitation: a review - Báez-Ferrer, Néstor; Izquierdo-Gómez, María Manuela; Marí-López, Belén; Montoto-López, Javier; Duque-Gómez, Amelia; García-Niebla, Javier; Miranda-Bacallado, Julio; de la Rosa Hernández, Alejandro; Laynez-Cerdeña, Ignacio; Lacalzada-Almeida, Juan (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Ischemic mitral regurgitation (IMR) is a frequent complication after acute myocardial infarction (AMI) associated with a worse prognosis. The pathophysiological mechanisms of IMR are not fully understood, but it is known to be a complex process in which ventricular remodelling is the main causal factor. The various imaging techniques in cardiology and echocardiography fundamentally have contributed significantly to clarify the mechanisms that cause and progressively aggravate IMR. At present, different therapeutic options, the most important of which are cardio-surgical, address this problem. Nowadays the improvement in cardiac surgery and transcatheter therapies, have shown a therapeutic advance in IMR management. IMR is a predictor of poor prognosis in patients with heart failure and depressed left ventricular (LV) systolic function. However, it remains controversial whether mitral regurgitation (MR) in these patients is a consequence of dilation and dysfunction of the LV, or whether it contributes to worsening the prognosis of the ventricular dysfunction. Given that echocardiography has a fundamental reference role in the identification, graduation of severity and evaluation of the therapeutics used in the treatment of MR, we are going to focus on it over the rest of the imaging techniques. In contrast to primary MR the benefits of mitral surgery in patients with secondary MR are uncertain. Therefore, we will comment fundamentally on the role of mitral surgery in patients with IMR, with an update of the different surgical interventions available, without forgetting to mention the other therapeutic options currently available.